Existence and computation of the set of positive solutions to polynomial matrix equations - Kaczorek, Tadeusz (1932- ); Łopatka, Rafał (Zielona Góra: Uniwersytet Zielonogórski)
Necessary and sufficient conditions are established for the existence of positive solutions to polynomial diophatine equations. A method of computing of the set of positive solutions to a polynomial diophatine equation based on extreme points and extreme directions is proposed. The effectiveness of the method is demonstrated on a numerical example.
Keywords: computation; set of positive solutions; polynomial matrix equation